Two new species of Phytoecia Dejean, 1835 (Coleoptera, Cerambycidae) from Iran - Faizi, Fardin; Danilevsky, Mikhail L.; Ghobari, Hamed; Nozari, Jamasb (Zootaxa, 2020)
Two new species are described from Iran: Ph. (Helladia) euimperialis Faizi & Danilevsky, sp. n. (Kurdistan prov., Marivan-county, Bardeh Sepi) and Ph. (s. str.) ambrusi Faizi & Danilevsky, sp. n. (Kurdistan prov., Marivan county, Chuin). Moreover, Phytoecia (Helladia) imperialis dorud (Sama, Rapuzzi & Rejzek, 2007) is elevated to species rank as Ph. (Helladia) dorud (Sama, Rapuzzi & Rejzek, 2007), stat. nov.